Sensitivity and Specificity of Urinary Hyaluronic Acid and Hyaluronidase in Detection of Bladder Transitional Cell Carcinoma - Jamshidian, Hassan; Hashemi, Mohsen; Nowroozi, Mohammad Reza; Ayati, Mohsen; Bonyadi, Mahdieh; Najjaran Tousi, Vahid (Urology Journal, 2014)
Purpose: To the assess sensitivity and specificity of urinary levels of hyaluronic acid (HA) and hyaluronidase (HAase) as an individual or a combined test to diagnose bladder transitional cell carcinoma (TCC). Materials and Methods: One hundred and ninety-four urine specimens were collected from individuals between July 2007 and March 2008. The urinary level of hyaluronic acid (HA) was measured by Enzyme-linked immunosorbent assay. Thereafter, the urinary levels of HA and HAase were normalized to urinary creatinine level and expressed as ng/mg and μ/mg. Results: Eighty percent of patients with bladder cancer had urinary HA level < 500 ng/mg, and 90% of controls showed HA level < 500 ng/mg (P < .001). The mean urinary levels of HA in controls did not vary significantly (P < .05), whereas they significantly increased (2.5 to 6.5 folds) in all grades of TCC. More than 80% of patients with grades 2 and 3 TCC had urinary HAase level < 10 μ/mg and over 80% of controls showed HAase level < 10 μ/mg (P < .05). Hyaluronidase levels increased in patients with grades 2 and 3 bladder TCC. Conclusion: Measurement of urinary levels of HA and HAase (with 89% sensitivity and 83% specificity) appears to be a highly accurate and non-invasive method for detecting bladder TCC and evaluating its grade.